Lang’s Survivals - Siegel, Jonah (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
Andrew Lang’s ideas on the nature and sources of originality seem fated for renewed attention due to the ways they appear to have forecast or anticipated modern attempts to get beyond the celebration of individual creativity. But rather than simply illustrating recent theoretical truisms, Lang’s formulations, whether developed in his writings on myth or in his texts devoted to literary topics, present subtle and not easily resolved challenges to attempts to dissolve individuality and agency into a greater communal whole. For Lang, because the effective use of material from the past to arrive at new forms is the measure of individual creativity, no work can ever make a claim to absolute originality. However, the prestige of the author, though hedged about by survivals from a lost past, is not for that reason lost. To recognize the tension between inherited material and new achievement is to begin to do justice to the historical place and conceptual force of the Andrew Lang effect.